Fatigue analysis of an energy storage supercapacitor box under random vibration loading - Xing Hu; Yupeng Tian; Shengqing Zhu; Jie Tang; Jinrun Cheng (Scientific Reports, 2025)
Abstract Supercapacitor is widely applied in braking energy recovery systems for urban rail vehicles. During the operation of urban rail vehicle, it is subjected to complex and highly random external vibration loads transmitted from the track surface. Long term exposure to such random vibrations could lead to fatigue damage. The previous studies mainly focus on the simulation of fatigue characteristics of battery packs, and there are relatively a few literature on simulation of the fatigue performance of energy storage supercapacitor box structures under random vibration loads. The fatigue life of an energy storage supercapacitor box applied to urban rail vehicle is studied in this paper. The first 10 modes of the supercapacitor box is calculate. The frequencies are all greater than 30 Hz. The supercapacitor box will not experience resonance. The fatigue characteristics within the frequency domain under random vibrations defined by ASDs is analyzed. The maximum fatigue damage of the energy storage supercapacitor box is 6.24 × 10− 6. The number of fatigue cycles is on an order of 105. Then the energy storage supercapacitor box is manufactured using lightweight aluminum alloy 6063-T5. The maximum fatigue damage of the aluminum energy storage supercapacitor box is 1.47 × 10− 4, with a fatigue cycle life of about 104 times. The fatigue life of the aluminum supercapacitor box could meet the requirements for low stress high cycle life of the urban rail vehicle components. The results could provide a basis for the structural design optimization of the energy storage supercapacitor boxes.